An agenda-setting study of national day coverage in state and national newspapers - Ting, Su Hie (Penerbit Universiti Kebangsaan Malaysia, 2017)
The paper describes an agenda-setting study of national day coverage in state and national newspapers. The specific aspects examined were the framing of the national day news in episodic or thematic terms, quotation of sources, and priming strategies. The theoretical framework of the study was the agenda-setting theory on how the salience attached to issues is influenced by the mass media. The media discourse data analyzed were 48 news articles related to national day that were published on 31 August 2016 in four newspapers. Textual analysis of the headlines and articles were conducted. The results showed that the national day articles were mainly in episodic frames, reporting particularly parades and events or competitions where the national flag is displayed. The thematic frames were mainly on the ordinary Malaysians’ experiences as well as those with links to the 1957 events. The newspapers deemed politicians as the most important source to quote for newsworthiness. The politicians played an important role in priming the readers or the Malaysians to appreciate what they have. One priming strategy was to bring up positive values on unity in diversity, patriotism and freedom which had been achieved due to the sacrifices of past Malaysians. The other priming strategy was mentioning or showing symbols of national identity, particularly the national flag and sometimes the national anthem, to invoke feelings of patriotism. The findings suggest that the Malaysian newspapers tell readers what and how to think about national identity and ethnic relations.